A second inheritance system: the extension of biology through culture. Issue 5 (18th August 2017) - Whiten, Andrew
Abstract : By the mid-twentieth century (thus following the 'Modern Synthesis' in evolutionary biology), the behavioural sciences offered only the sketchy beginnings of a scientific literature documenting evidence for cultural inheritance in animals—the transmission of traditional behaviours via learning from others (social learning). By contrast, recent decades have seen a massive growth in the documentation of such cultural phenomena, driven by long-term field studies and complementary laboratory experiments. Here, I review the burgeoning scope of discoveries in this field, which increasingly suggest that this 'second inheritance system', built on the shoulders of the primary genetic inheritance system, occurs widely among vertebrates and possibly in invertebrates too. Its novel characteristics suggest significant implications for our understanding of evolutionary biology. I assess the extent to which this second system extends the scope of evolution, both by echoing principal properties of the primary, organic evolutionary system, and going beyond it in significant ways. This is well established in human cultural evolution; here, I address animal cultures more generally. The further major, and related, question concerns the extent to which the consequences of widespread animal cultural transmission interact with the primary, genetically based inheritance systems, shaping organic evolution.